Western element in the vascular flora of Poland - Zając, Maria; Zając, Adam (Biodiversity: Research and Conservation, 2006)
The western element in the Polish flora was determined by using published cartograms of distribution of vascular plants in Poland. The species that reach their eastern, southeastern or northeastern limits in Poland were taken into account, except mountain taxa and the species whose limits roughly coincide with Polish borders or partly reach outside the Polish territory. Three distribution range groups of native plants and one of anthropophytes were identified. Possible correlations between general ranges and affiliations to one of the studied elements were tested. Affiliations of the classified elements to large syntaxonomic units were also studied.